2009
DOI: 10.1590/s1806-37132009001000003
|View full text |Cite
|
Sign up to set email alerts
|

Preditores da dessaturação do oxigênio no teste da caminhada de seis minutos em pacientes com fibrose cística

Abstract: Objective: To identify the predictive factors of oxygen desaturation during the six-minute walk test (6MWT) in patients with cystic fibrosis (CF). Methods: Prospective cross-sectional study involving clinically stable patients with CF aged ≥ 10 years. The patients were submitted to nutritional evaluations, oral glucose tolerance tests, pulmonary function tests, chest X-rays and 6MWTs. Results: The study included 88 patients (43 females and 45 males; mean age, 19.9 ± 7.2 years; mean FEV 1 , 65.4 ± 28.4%). We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…We also observed that CF patients reported only mild to moderate dyspnea during the 6MWT, despite significant impairment in pulmonary function, suggesting that these patients had a blunted perception of dyspnea (20). In CF patients, dyspnea is of particular interest, since it may be a sign of severe pulmonary disease or nonpulmonary disease.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We also observed that CF patients reported only mild to moderate dyspnea during the 6MWT, despite significant impairment in pulmonary function, suggesting that these patients had a blunted perception of dyspnea (20). In CF patients, dyspnea is of particular interest, since it may be a sign of severe pulmonary disease or nonpulmonary disease.…”
Section: Discussionmentioning
confidence: 75%
“…In another study (20), we observed that CF patients reported only mild to moderate dyspnea during the 6MWT, despite significantly impaired pulmonary function. One hypothesis generated from these findings was that the subjective perception of the patients discriminates the severity of their disease when it is mild.…”
Section: Introductionmentioning
confidence: 75%
“…Pelegrino et al examined the influence of lean body mass on cardiopulmonary repercussions during the six-minute walk test in patients with COPD 7. Ziegler et al looked at predictors of oxygen desaturation during the six-minute walk test in patients with cystic fibrosis 45. Oliveira et al reviewed the relationships between the walk test, pulmonary function tests and length of hospitalization in cardiac surgery patients 5.…”
Section: Methodsmentioning
confidence: 99%
“…COMPARAÇÕES O TC6 constitui valioso indicador de limitação de AVD e pode ser utilizado para avaliação de dessaturação de oxigênio induzida por exercício. (40) Apesar das controvérsias quanto ao uso da DP6 ou da diminuição do oxigênio como variável de correlação para função pulmonar, o TC6 tem-se mostrado eficiente na avaliação da efetividade da terapia em pacientes com doença intersticial pulmonar, hipertensão pulmonar idiopática e seguimento de reabilitação pulmonar. É, inclusive, um marcador criterioso para indicação de transplante pulmonar ou oxigênioterapia suplementar.…”
Section: Indicações Do Tc6unclassified